Delayed Hemiarthroplasty in Elderly Patients With Intertrochanteric and Femoral Neck Fractures - Mohsen Mardani-Kivi; Ehsan Kazemnejad Leili; Zahra Haghparast Ghadim-limudahi; Zohre Darabipour; Zoleikha Azari (Negah Institute for Scientific Communication, 2021)
Introduction: In developing countries, the hemiarthroplasty surgical procedure is applied for many patients with hip fractures. These surgical interventions occur with a delay because of various reasons, including insufficient hospital facilities and the deficiency of the ICU beds. Therefore, this study aimed to assess the consequences and complications of delayed hemiarthroplasty in the elderly (>60 years of age) with intertrochanteric and femoral neck fractures, regarding a 1-year follow-up.  Methods: This retrospective cross-sectional study evaluated 392 patients (59.2% female and 40.8% male; Mean±SD age: 69.9±4.7 years) according to the presence or absence of postsurgical complications, including the limbs shortening, infection, hematoma, symptomatic pulmonary embolism, Harris hip score, and the number of deaths following cemented bipolar hemiarthroplasty.  Results: The majority of the patients (82.9%) underwent surgery in public hospitals, and 34% of them had femoral neck fractures. The evaluation of the trauma-surgery time interval index revealed that 39% of patients had delayed surgery (24% of which received surgery on the third day and 15.1% on the fourth day after hospital admission). The trauma-surgery time interval was significantly associated with infection (6.6%), hematoma (4.1%), embolism (2.8%), and deep vein thrombosis (4.8%) (P<0.05). The mortality rate was 0.5% (2 cases), 1% (4 cases), and 1.3% (5 cases) in the first month, 1 to 6 months, and 6 to 12 months, respectively. Also, in the first month, this analysis showed a significant (P<0.05) association between mortality rate and increased trauma-surgery time interval. According to the functional outcomes, patients with delayed surgery represented the decreased levels of Harris hip score. Conclusion: Rapid preparation of elderly patients for hemiarthroplasty is considered an effective factor to reduce morbidity and mortality rates.